Radiation-induced meningioma following radiation therapy for pituitary adenoma: a case report - Muhammed Nordin, Ellyda; Jalaludin, Win Mar @ Salmah (The Faculty of Medicine, International Islamic University Malaysia, 2013)
It is well known that ionozing radiation has an onco-genetic activity and has been implicated in the causation of brain tumors. However, when a new growth appears adjacent to the site of previous tumor, the diagnosis is more toward recurrence. In addition to that, the possible cause might be overlooked when it occurs many years after radiation treatment. We report a case of radiation-induced meningioma developed 20 years after the patient received radiotherapy for pituitary adenoma.